Projecto de reabilitação de uma Casa em Afife: notas sobre o processo de transformação de um lugar - André Filipe Pipa Afonso Covas (2018)
In this thesis we reflect upon the process that accompanied the projectfor the refurbishment of a house in Afife, in the province of Vianado Castelo. Along the way, we describe the author's encounter withthe innumerous circumstances that define the space of the projectwhile meditating about some of the fundamental issues inherent tothe act of inhabitation and its connection with the built environment.While wandering between practice and research, we seek to buildthe foundations of a critical discourse that aims to inform the project.By approaching a real context framework, the proposition for thetransformation of this place reflects the possible synthesis betweenpersonal convictions about the architectural practice and the limitsof reality.